Penggunaan Model Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar Siswa - Naris Naris (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The research objective to be achieved is to find out the improvement of learning outcomes and the ability of Students About Organizational Learning for fifth grade students of SD Negeri 3 Dermaji UPK Lumbir through the Contextual Teaching and Learning (CTL) Learning Model. With the use of the Contextual Teaching and Learning (CTL) learning model in this class action research results can be obtained: 1) the average value of the formative test results of students' ability about Organizational Learning students in pre-cycle is 60, in cycle I rises to 70. In the cycle II got an increase in the average value of students to 80. 2) The percentage of mastery learning students in the first cycle who received grades in accordance with KKM, as many as 69% of 13 students, 9 students. In the second cycle there was a significant increase in the completeness of student learning outcomes 92% or 12 out of 13 students completed learning, based on the information above, a conclusion can be drawn as follows: Through the use of Learning Models (CTL) can improve students' ability about Organizational Learning Class V Students of Semester II Elementary School 3 Dermaji UPK Lumbir Banyumas Regency 2015/2015 Academic Year.